Structural damping estimation from live monitoring of a tall modular building - Fitzgerald, Breiffni; Broderick, Brian; Hickey, John; Moore, Hollie (My University, 2023)
The damping ratio is a key indicator of an individual structure's susceptibility to dynamic loads, including the level of discomfort experienced by the occupants of a tall building subjected to wind loading. While computational models, laboratory stud- ies and empirical data can provide estimates of structural damping, the most reliable way to evaluate true damping ratio values is through modal identification using data from field tests on full-scale finished structures. As an innovative form of construc- tion, high-rise modular buildings have not been the subject of previous vibration monitoring investigations, implying an absence of essential structural dynamics infor- mation. This paper assesses the reliability of four modal identification methods for estimating the damping ratio of a structure using ambient acceleration response data recorded from the world's tallest modular structure, the Ten Degrees building in Croydon, South London. The methods considered are two implementations of the Bayesian fast Fourier transform (BFFT), the random decrement technique (RDT), and a hybrid of the RDT which first decomposes the ambient data into sub-signals using analytical mode decomposition (AMD-RDT). Each method is applied to response data collected during 10 significant wind loading events to evaluate the inherent modal properties of the structure, with the computed damping ratio values compared between methods and events. By reporting the first measured damping ratios for a tall modular structure, the paper makes an important contribution to knowledge about the vibration properties of an emerging form of construction.
PUBLISHED
Keywords: Wind-induced acceleration response; Tall volumetric modular construction; Tall buildings; Modal identification methods; Damping ratio; Ambient vibration monitoring; Smart & Sustainable Planet; Structural Dynamics; Structural Engineering; WIND